Profilaktika chroniceskogo fiziceskogo perenaprjazenija junych sportsmenov po dannym zitochimiceskoj ekspertizy - Poljakov, S. D.; Korneeva, I. T.; Petricuk, S. V.; Gogotova, V. L.; Chruscev, S. V.; Siscenko, V. M. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2006)
On the data of the cytochemical examination the Authors have investigated the opportunity of directed use of preparations of metabolic action for THE development of an algorithm of the preventive maintenance of the chronic physical overstrain at young athletes.